PENGARUH KEPATUHAN WAJIB PAJAK, PEMERIKSAAN PAJAK DAN SANKSI PERPAJAKAN PADA PENERIMAAN PPH PASAL 25 WAJIB PAJAK BADAN: The Influence of Taxpayer Compliance, Tax Audit and Tax Sanctions on Revenue of Income Taxpayer Article 25 Corporate Taxpayer - Sifora Mardalena Metawati Harita; Juaniva Sidharta (Universitas Kristen Indonesia, 2023)
The importance of pajak in the nation's economic development is a motivating factor for the Directorate of Jendral Pajak (DJP) to increase pajak receipts. Due to this, DJP takes a variety of initiatives to increase pajak penerima every year, such as promoting socialization of pajak as crucial to improving the nation's economy. The purposes of these studies are to determining effect of tax payer compliance, tax inspection and tax sanctions on receipt of Incoming Tax Article 25 inKPP Pratama Jakarta Kramatjati. The sample used in this research is taxpayers register in KPP Pratama Jakarta Kramatjati use a sample technique known as Purposive Sampling. Analytical methods currently use is a quantitative method. The current study utilizes primary and customer data which may be obtain from a number of sourcing, include KPP Pratama Jakarta Kramatjati, as well as data collections in the forms of questionnaire sent to tax payers who have register in KPP Pratama Jakarta Kramat Jati. The survey results based on descriptive statistics show that tax obligation compliance, tax inspection and tax sanctions of KPP Pratama Jakarta Kramatjat are good. Validity and reliability tests were also used in this study; classical standard tests were normality tests, multi collinearity tests, auto correlation tests, heteros cedasticity tests, tests, F tests and coefficient-determination tests. Hypothesis testing in these studies use multipled regressions analyst techniques. Results of testing the hypothesis partially of taxpayer compliance, tax inspection have a positive and significancy effects on receipt of incoming tax articles 25 of the corporate taxpayer, while tax sanctions do not significancy affects the income tax revenue of article 25 corporates taxpayers. The results of simultaneous testing of taxpayer compliances, tax inspection and tax sanctions have a positives and significancy effects on receipt of Incoming Tax Articles 25 Corporates Tax payers. Keywords: Income Tax Article 25, Taxpayers, Tax Inspections, Tax Sanctions, Tax Revenues